KUALITAS FUNGSI SOSIAL TERHADAP KEBERADAAN TAMAN KOTA PUBLIK DI KOTA SURAKARTA - Prasetyo Febriarto (UNHI Press, 2019)
The purpose of this study was to find out the utilization of green open space by looking at the aspects of socialfunctions in the form of recreational activities of park users towards the existence of Taman Monumen 45 Banjarsari(Monjari) city park in Surakarta City. The object of this research is users with various social functions in the form ofactivities in City Parks in Surakarta City, namely, Taman Monumen 45 Banjarsari (Monjari). Data retrieval techniquesuse information collected, namely information and data relating to social functions of City Parks in Surakarta City. Thisinformation and data is obtained from various sources, in the form of magazines, scientific journals, websites (internet)and books that are relevant to the object of research. The analytical method used in this study uses explorative descriptiveanalysis. Conducted by observation, observation of the social function of the existence of city parks on user activities byanalyzing user activity activities that occur outside and inside the city park in the monument of Taman 45 Banjarsari(Monjari). The study was conducted to find out the social functions (user activity) that occur for five days (Tuesday toSunday) starting from morning (07.00 - 09.00 am), afternoon (12.00-14.00 am), and afternoon (15.00 - 17.00 pm) to showthe city park good quality and ideal in the city park.